Grupa Pro Arte – prezentacja wstępna - Pawłowska, Aneta (Acta Universitatis Lodziensis. Folia Historica, 2002)
Pro Arte, active in the years 1922-1932, associated many prominent artists, among others: Stanisław Bagieński, Tadeusz Cieślewski (senior), Zdzisław Jasiński, Jan Kotowski, Bronisław Kopczyński, Stanisław Zawadzki, Piotr Krasnodębski, Apoloniusz Kędzierski, Wojciech Kossak, Stanisław Straszkiewicz, Teodor Ziomek, Józef Rapacki, Czesław Tański, Henryk Piątkowski, Władysław Wankie, Henryk Weyssenhoff, Stefan Popowski. The artistic programme of the group is rather difficult to grasp. The goals expressed in the group’s introductory manifesto are limited to a few cliches, which included working for the sake of art, maintaining the continuity of artistic tradition and social respect. The group’s most unfiuential personalities were Popowski, Piątkowski and Wankie. These artists published numerous works in Warsaw press (Popowski and Wankie), and made names for themselves by writing monographes of such artists as Władysław Podkowiński, Władysław Czachórski, Elwiro Andriolli (Piątkowski). Particularly valuable for art historians was the work of Wankie, who was the author of a report on the life of a Polish artistic colony on the river Izara. In that report, hę presented the trends and tendencies dominating in Munich towards the end of the 19lh century. He was also the author of a comparative study of two masters of Polish painting, Matejko and Chełmoński. The main motifs recurring in the works of Pro Arte group’s artists can be divided into several categories. The most popular of them was landscape painting, although portraits, urban landscapes, still lives, fork scenes, battle scenes and allegories are also numerous. Pro Arte group is an exceptionally interesting, although little-known, example of coexistence on the art stage of the Second Polish Republic of certain forms of art, usually deemed backward when compared with the so-called avant-garde trends. It must be emphasised, however, that the extents of audience’s interest in both these visions of the world were exactly opposite to the number of studies that analyse them today.